Challenges and Prospects of Legal Regulation on the Way to the Innovative Type (On the Example of the Republic Of Belarus) - Shafalovich, Нanna (Teisė, 2018)
[only abstract in English; full article, abstract in Russian]The movement towards the formation of the state and the law of the innovative type poses new challenges, for an adequate response to which the entire system of legal regulation needs to be updated. The change of priorities in the legal regulation gives rise to perspectives, which generally point to a greater balance of the law of the innovative type. Unlike other types of states, a state with a strategically innovative function (an innovative state) takes on the task of promising legal regulation of the public relations. For the legal regulation ‘‘on the lead’’ (perspective) will require a change in the entire system of the legal regulation. In particular, it will require among other measures the legalization and the expansion of the range of sources of law, its addition to auxiliary sources of law of a new type, close to legal doctrine. These include general legal principles, the understanding of law, the tendencies of the law development, the legal facts theory.In conditions of formation of the law of innovative type the following the legal regulation meets the following challenges:First, innovation development is confronted with a contradiction in the concept of a free market and central planning;Secondly, the innovative state should achieve an outstripping effect from the legal regulation (especially the innovation sphere);Thirdly, states that are receptive to innovation are characterized by the inevitable complication of legal ties;Fourthly, the requirement of constant renewal of the law exacerbates the problem of balancing the ever-increasing dynamism and the stability of legal regulation;Fifth, legal regulation in innovative states will require modernization and democratization.The adoption of measures to adapt the legal regulation system to the requirements of an innovative type of law makes it possible to single out the following perspectives:1) “Denationalization”, the transition from the actual state monopoly to the sources of the law to “private-state partnership”, i.e. alignment and mutual influence of the sources created by the state and authorized by it;2) Legalization of the entire system of sources of law (including the Republic of Belarus) through legislative consolidation and recognition of basic and auxiliary sources of law de jure, and not de facto, as it is now;3) The balance of individual and normative types of legal regulation, eliminating the disproportion between the law-making and law-realizing (law-enforcement) stages of the legal regulation mechanism;4) Increasing the role of dispositive norms that involve the use of more flexible sources of law alternative to direct legal establishment;5) Redistribution of the main burden in legal regulation from the state to non-state entities (supranational and “sub-state”) by changing the ratio of governance and self-government, centralization and decentralization.
Keywords: none